Chemical Reactions in Inorganic Chemistry - Chandraleka, Saravanan (IntechOpen, 2018)
The book "Chemical Reactions in Inorganic Chemistry" describes an overview of chemical reagents used in inorganic chemical reactions for the synthesis of different compounds including coordination, transition metal, organometallic, cluster, bioinorganic, and solid-state compounds. This book will be helpful for the graduate students, teachers, and researchers, and chemistry professionals who are interested to fortify and expand their knowledge about sol-gel preparation and application, porphyrin and phthalocyanine, carbon nanotube nanohybrids, triple bond between arsenic and group 13 elements, and N-heterocyclic carbene and its heavier analogues. It comprises a total of five chapters from multiple contributors around the world including China, India, and Taiwan.